A Rare Case of Nasopalatine Duct Cyst Diagnosed 7 Years After Secondary Bone Grafting in a Patient With Cleft Lip and Palate - Kazuyuki Yusa; Satoshi Kasuya; Nobuyuki Sasahara; Tomoharu Hemmi; Shigeo Ishikawa (Case Reports in Dentistry)
Secondary autogenous particulate cancellous bone and marrow grafting (SBG) is a reliable and established technique for patients with alveolar cleft. Some reports have described complications after SBG, but cyst formation in alveolar bone where SBG has been performed appears to be extremely rare. Herein, we report a rare case of a cyst forming at a grafted site 5 years after SBG. A 15-year-old girl was referred to our clinic with a chief complaint of swelling in the right maxilla. The patient had a history of multiple surgeries for cleft lip and palate. Panoramic radiography and computed tomography (CT) revealed a radiolucency in the right maxilla, at the site where SBG had been performed. Enucleation of the lesion and bone graft using particulate cancellous bone and marrow were performed. The histological diagnosis was a nasopalatine duct cyst. Postoperatively, no signs of recurrence have been observed. Some reports have suggested that damage to the incisive canal can lead to the formation of nasopalatine duct cysts. SBG thus needs to be performed with care, as invasion of the incisive canal during the procedure may result in cyst formation and the need for additional surgery.